2002
DOI: 10.2527/2002.8041020x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dietary conjugated linoleic acid on growth, meat quality, lipogenesis, plasma leptin and physiological variables of lipid metabolism in rabbits1

Abstract: ABSTRACT:We investigated the effects of conjugated linoleic acid (CLA) supplementation on growth, feed efficiency, carcass characteristics, meat quality, lipogenesis, and lipid metabolism in rabbits. One hundred forty-four New Zealand White rabbits, half males, half females, age 55 d, mean 1.8 kg BW, were randomly assigned to three weight-and sex-balanced feeding groups in which conventional pelleted diets were supplemented with 0, 0.25, or 0.5% of a CLA preparation. The CLA preparation contained 65% CLA isome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
50
1
10

Year Published

2004
2004
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 39 publications
10
50
1
10
Order By: Relevance
“…It has not been clearly established which specific CLA isomers are responsible for the various biological effects, however; the cis-9,trans-11 isomer is thought to play the key role in the antiatherogenic and anticarcinogenic activities (Corino et al, 2002;Bauman et al, 2003). As expected, therefore, the cis-9,trans-11 isomer supplied to the diet (Group 4) had no influence on body mass gain, while the pre- sence of this isomer in the Se-supplemented diet insignificantly counteracted the decrease of body mass gain from the Se dose (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has not been clearly established which specific CLA isomers are responsible for the various biological effects, however; the cis-9,trans-11 isomer is thought to play the key role in the antiatherogenic and anticarcinogenic activities (Corino et al, 2002;Bauman et al, 2003). As expected, therefore, the cis-9,trans-11 isomer supplied to the diet (Group 4) had no influence on body mass gain, while the pre- sence of this isomer in the Se-supplemented diet insignificantly counteracted the decrease of body mass gain from the Se dose (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous CLA isomers are possible depending on the position of the double bond pairs (e.g., 7-9, 8-10, 9-11, 10-12) (Corino et al, 2002). The geometrical configuration of the double bonds can also vary to increase the number of possible isomers: trans-trans, cis-trans, trans-cis and cis-cis.…”
Section: Introductionmentioning
confidence: 99%
“…11) In addition, Lin et al 49) have reported that a trans-10, cis-12 CLA treatment decreased the synthesis of TG and the secretion of Hep G2 cells. Corino et al 35) have reported that dietary CLA increased the plasma concentration of HDL cholesterol and decreased that of LDL cholesterol in rabbits. In addition, the IGF-1 level was also affected by a trans-10, cis-12 CLA treatment in an HT-29 cell culture experiment.…”
Section: Discussionmentioning
confidence: 99%
“…35) Many studies have reported that dietary supplementation with a linoleic acid-rich oil such as corn oil, 36) soybean oil 37) or safflower oil 38) increased the concentration of CLA in the ruminant. Similarly, in the present study using high-quality ESB, and the total CLA concentration in the body fat was significantly higher in the HTMT-treated and non-HTMT-treated dietary groups than in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…De fato, pesquisadores objetivando estudar essa relação demonstram que o consumo de CLA reduz os níveis sanguíneos de leptina em ratos OLETF 119 e ratos Sprague-Dawley 125 . Esses efeitos, contudo, não foram observados por Corino et al 71 e Medina et al 126 , cujos trabalhos foram realizados com humanos e coelhos, respectivamente. Mesmo que controversos, os estudos supracitados fornecem subsídios para especular sobre a ação do CLA no controle da sinalização celular e, conseqüentemente, na produção dessa adipocitocina tão importante para o controle da ingestão alimentar.…”
Section: Cla Metabolismo De Glicose E Lipídeos E Composição Corporalunclassified